2018
DOI: 10.1097/brs.0000000000002459
|View full text |Cite
|
Sign up to set email alerts
|

Which Domains of the ODI Best Predict Change in Physical Function in Patients After Surgery for Degenerative Lumbar Spondylolisthesis?

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Conflicting evidence exists as to whether these instruments correlate with one another in specific spinal pathologies. [5][6][7] Clinically, the goal is to measure patient outcomes in the least burdensome way. Many spine centers have historically collected SF-36 for many years, and the question of whether it is ''safe'' to switch to the less burdensome SF-12 for long-term follow up has not been answered.…”
Section: Introductionmentioning
confidence: 99%
“…Conflicting evidence exists as to whether these instruments correlate with one another in specific spinal pathologies. [5][6][7] Clinically, the goal is to measure patient outcomes in the least burdensome way. Many spine centers have historically collected SF-36 for many years, and the question of whether it is ''safe'' to switch to the less burdensome SF-12 for long-term follow up has not been answered.…”
Section: Introductionmentioning
confidence: 99%
“…For the first time, Farfan H. et al revealed a significant correlation between tropism of FJs and the formation of IVD hernias in the lumbosacral spine. 24 Also, the authors point out that the hernias of the lumbar IVD appear on the side of FJs with the smallest angle, since with this orientation of FJs, it is not capable of reducing torsion loads affecting on the fibrous ring during movement. 16,25 Clinical studies are currently underway to investigate the relationship between tropism and the orientation of FJs with the onset of degenerative spondylolisthesis.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, many studies have confirmed the impact of angulation and tropism of FJs on the biomechanics of the spinal column. [23][24][25] However, no correlation has been made with the remote clinical outcomes of these neuroimaging parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative assessment of the patients' psychological characteristics, by filling out questionnaires and scales, allows us to identify factors that have predicative effect on the result of surgical treatment. The effectiveness of surgical treatment is estimated by a change in the Oswestry index, 23,24 reduction of pain syndrome as measured by the VAS scale, and changes in the parameters of other psychological scales (Catastrophization scale, Pain Coping Index, etc.). [25][26][27] However, only the Oswestry index has recommendations for interpreting changes in the index, which is necessary to evaluate the effectiveness of treatment.…”
Section: Contribution Of the Authorsmentioning
confidence: 99%